Difference Results Study Mathematics And Activity Study Using Learning Models Cooperative Type Teams Games Tournament (TGT) and Numbered Heads Together (NHT) on Material Operation Count Algebra - Ashari, Mila Dwi Nanda; Lumbantobing, Happy; Hadiyanti, Yosefin Rianta; Kho, Ronaldo; Sitepu, Rina Ananta (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to investigate the disparities in mathematics learning outcomes of students instructed through the Teams Games Tournament (TGT) and Numbered Heads Together (NHT) cooperative learning methods concerning algebraic arithmetic operations. The study was conducted at SMP Muhammadiyah Jayapura. This research employs an experimental design using counterbalancing. The study population comprised class VII of SMP Muhammadiyah Jayapura during the 2024/2025 academic year, with the research sample consisting of classes VII-B and VII-C, each containing 34 pupils. The sample selection employed a purposive sampling method. Data on learning outcomes were obtained through a validated assessment instrument. We analyzed the pretest and posttest scores to derive normalized learning outcome values (N-gain). Due to the non-normal distribution of the data, we evaluated the N-gain value using non-parametric statistics via the Wilcoxon test. The study's results showed a significant difference in learning outcomes between the Teams Games Tournament (TGT) and Numbered Heads Together (NHT) cooperative learning models, with a sig. ρ value of 0.401, which is higher than 0.05. The mean N-gain value in Teams Games Tournament (TGT) (0.93) surpassed the mean N-gain value of Numbered Heads Together (NHT) (0.92). The study's results indicated that student engagement in learning through the Numbered Heads Together (NHT) method surpassed that of the Teams Games Tournament (TGT) model. The disparity in activity was substantial according to the Wilcoxon test, with a significance level of sig. ρ = 0.705.